Silver nanoparticle synthesis using pineapple waste / Syafiza Abd. Hashib, Syed Muhammad Zulfazli Syed Omar and Ana Najwa Mustapa - Abd. Hashib, Syafiza; Syed Omar, Syed Muhammad Zulfazli; Mustapa, Ana Najwa (Universiti Teknologi MARA Shah Alam, 2018)
Silver nanoparticles has been recognised to have numerous advantages for medical, cosmetics and environmental applications. There are three methods to produce nanoparticles namely physical, chemical, and biological. Biological method is preferred because of its eco-friendly, safer, and low operation cost. Usually, plant parts or microorganism used as raw material in biological synthesis. However, plant part is most preferred material due to its simplicity compared to microorganism technique. In this work, silver nanoparticles were synthesised using pineapple peel extract as reducing agent. High phenols content of pineapple extract indicates its potential as reducing and capping agent in the synthesis of silver nanoparticles. The synthesised silver nanoparticles were characterised by FTIR, UV-Vis, and FESEM to verify the presence of nanoparticles. Results demonstrated that the size of AgNPs was formed in range from 20 nm to 30 nm and this work has proven that the pineapple peel has potential in the silver nanoparticles synthesis.